Cu2+ intercalation activates bulk redox reactions of MnO2 for enhancing capacitive performance. (August 2020) - Hu, Lingyuan; Gao, Rui; Zhang, Anqi; Yang, Ru; Zang, Xiaogang; Wang, Shiyu; Yao, Shuyun; Yang, Zhiyu; Hao, Haigang; Yan, Yi-Ming
Abstract: Activating bulk redox reaction is important for enhancing capacitive performance. Here, Cu 2+ intercalated δ-MnO2 is prepared through an ion exchange strategy to activate the bulk redox reaction. The sample shows an average Mn valence state of 3.01 and an increased electrical conductivity of 2.67 × 10 −4 S cm −1 . The bivalent cation intercalation structure shows higher diffusion-controlled contribution than the counterpart. Density functional theory calculation suggests that intercalated Cu 2+ endows birnessite with metallic characters by enhancing the density of state around Fermi level. Bader charge analysis demonstrates that Cu 2+ intercalation decreases the average Mn valence state, thus creating more redox-active sites in bulk MnO2 . This work not only establishes a reliable method for activating bulk redox reactions for further improving the specific capacitance of MnO2 -based electrodes, but also provides new insights on understanding the charge storage mechanism of MnO2 . Graphical abstract: Cu 2+ intercalation decreases the average Mn valence state, thus providing more redox-active sites for energy storage. Intercalated Cu 2+ endows birnessite with metallic characters and high electrical conductivity by enhancing the density of state around Fermi level. Both the decreased average Mn valence state and improved electrical conductivity activate bulk redox reactions of MnO2 through enhanced diffusion-controlled contribution. Image 1 Highlights: Cu 2+ intercalation induced low average Mn valence state of 3.01 and high electrical conductivity of 2.67×10 -4 S cm -1 . Cu(II)-birnessite exhibits a specific capacitance of 360.1 F g -1 at 1 A g -1 with a 19.5% diffusion controlled contribution. Intercalated Cu 2+ endows birnessite with metallic characters by displaying a continuous density of state around Fermi level. Both the decreased average Mn valence state and increased conductivity provide redox-active sites in the bulk MnO2 .